The contents and forms of public-private partnership methods in infrastructure branch (on the example of the Republic of Kazakhstan) (Journal of Economic Research & Business Administration, 2016)
The article deals with the role of infrastructure branches of the Republic of Kazakhstan and tasks in the direction of their modernization and development. The conclusion is drawn that an actual task in the direction of modernization and development of infrastructure branches of the Republic of Kazakhstan is search of sources of financing of construction and functioning of infrastructure facilities. Advantages of public-private partnership to development of infrastructure branches are defined. On the basis of the analysis of an infrastructure complex of the Republic of Kazakhstan the author defined potential projects in the field of public-private partnership. The factors constraining development of public-private partnership in infrastructure branches of economy of the Republic of Kazakhstan are systematized and classified. The model of interaction of the state and enterprise structures in development of infrastructure branches of economy of the Republic of Kazakhstan is offered and the main instruments of its realization are defined.
Keywords: public-private partnership; project; mechanism; infrastructure; branch.